A magyar bírósági szervezet területi elhelyezkedésének ellentmondásai - Kengyel, Miklós (Tér és Társadalom, 1989)
There have been essential changes in Hungarian judiciary following World War II. The fourlevel judicial organization has been simplified into a three-level one, following the Soviet model of judiciary. As a result, the 'accessibility' of judiciary could have improved, since the rules of authority and competence and the judicial procedure have become more clear-cut. But a process of amalgamation of small district courts started during the 1950s and thereby the number of basic courts has shrunk from 151 to 93 by now. The spatial pattern of judiciary is rather contradictory. Reducing the number of district courts was always argued for by increasing efficiency while the nettlement geographical features of judiciary (like the areal size of circumscriptions, the number of population or the population density) were completely disregarded. As a result, the 'accessibility' of judiciary has deteriorated. The present paper reviews changes ín the settlement geographical features of Hungarian judiciary from 1945 onwards. It touches upon the situation which evolved following the abolishment of districts leading to a partfal separation of judicial and administrative spatial breakdown. The chapter on 'Abridged Hungarian judicial geography' describes present judiciary as reflected by leading settlement geographical factors, using tables and figures. The paper concludes by analysing possible future changes.